2010
DOI: 10.1080/01496390903423899
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Subcritical Water Extracts from Chaga Mushroom (Inonotus obliquus)

Abstract: The subcritical water (SCW) extraction of Chaga mushroom (CM) was carried out at various temperatures (50, 100, 150, 200, 250, and 300 C) and times (10, 30, and 60 min), and then antioxidant activities of the SCW extracts were evaluated by determining 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity, reducing power (RP), superoxide dismutase (SOD)-like activity, and total phenol content (TPC). The DPPH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…6). These data are in agreement with the increase in SOD‐like activity at high temperature found in Chaga mushroom ( Inonotus obliquus ) 23…”
Section: Resultssupporting
confidence: 90%
“…6). These data are in agreement with the increase in SOD‐like activity at high temperature found in Chaga mushroom ( Inonotus obliquus ) 23…”
Section: Resultssupporting
confidence: 90%
“…ABTS radicals are scavenged by antioxidants by donating hydrogen ions and assessed by determining the decrease in absorption at 405 nm (Seo and Lee 2010). The ABTS radical scavenging activities of SCW extracts, methanol extracts, and L-AA (positive control) are shown in Table 4.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In contrast to common methods, SCW is an environmentally friendly technique; SCW also entails lower costs of extracting agents, produces higher extract quality, and reduces extraction time. Studies have also shown that SCW is an effective method used to extract polyphenols from plants (Budrat and Shotipruk 2009;Seo and Lee 2010;Kim et al 2009;Rodríguez-Meizoso et al 2006). Budrat and Shotipruk (2009) showed that the total phenolic contents obtained from bitter melon by SCW at 200°C is seven times as high as those produced by MeOH extraction.…”
Section: Introductionmentioning
confidence: 96%
“…These bioactive compounds have been known to have antioxidant, anti-inflammatory, anti-cancer, hypoglycemic, anti-virus, and other functional activities (Zhong et al, 2009). Especially, phenolic compounds in chaga mushroom are known to have strong antioxidant activities related to therapeutic effects against diseases associated with oxidative stress such as cardiovascular diseases, diabetes, and cancer (Seo & Lee, 2010;Khatua et al, 2013).…”
Section: Introductionmentioning
confidence: 99%